2017
DOI: 10.1080/23744006.2017.1393986
|View full text |Cite
|
Sign up to set email alerts
|

Drawing-based deception detection techniques: a state-of-the-art review

Abstract: Drawing-based deception detection techniques 2 AbstractThe current article presents a concise overview of the emerging literature on drawingbased deception detection techniques. We cover the theoretical rationale of such techniques as well as the main results from the extant empirical studies. These studies have primarily looked at differences in the drawings between truth tellers and liars in terms of quality (e.g., detail, plausibility) and consistency (both within-group, and between-statement). The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 48 publications
0
26
1
Order By: Relevance
“…From a more practical point of view, the results can relate to recent work in drawing‐based deception detection techniques. The use of drawings is a promising innovation for detecting deception, which has resulted in some of the largest cues to deceit in the published deception literature (for a review, see Mac Giolla, Granhag, & Vernham, ). The underlying theoretical rationale for the predicted differences between liars' and truth tellers' drawings is, however, somewhat difficult to readily translate to intention contexts.…”
Section: Discussionmentioning
confidence: 99%
“…From a more practical point of view, the results can relate to recent work in drawing‐based deception detection techniques. The use of drawings is a promising innovation for detecting deception, which has resulted in some of the largest cues to deceit in the published deception literature (for a review, see Mac Giolla, Granhag, & Vernham, ). The underlying theoretical rationale for the predicted differences between liars' and truth tellers' drawings is, however, somewhat difficult to readily translate to intention contexts.…”
Section: Discussionmentioning
confidence: 99%
“…One such interview tool is the use of drawings. In their overview of deception studies that used drawings, Mac Giolla, Granhag, and Vernham () reported that differences between truth tellers' and liars' drawings frequently occur. They concluded that the use of drawings has potential to detect detection.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the use of drawings has potential to detect detection. In all studies summarized by Mac Giolla et al (), sketching occurred in isolation of speech. That is, participants were never asked to narrate and sketch at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding real‐life interviewing settings, the application of mnemonics can be valuable because they do not require many resources (e.g., in contrast to polygraph machines) and are easy to implement and analyse (Mac Giolla, Granhag, & Vernham, ; Vrij et al, ). Thus, these techniques can be useful for practitioners to make inferences about the credibility of interviewees.…”
Section: Introductionmentioning
confidence: 99%